2022
DOI: 10.1016/j.nbd.2021.105585
|View full text |Cite
|
Sign up to set email alerts
|

ALS-linked cytoplasmic FUS assemblies are compositionally different from physiological stress granules and sequester hnRNPA3, a novel modifier of FUS toxicity

Abstract: Formation of cytoplasmic RNA-protein structures called stress granules (SGs) is a highly conserved cellular response to stress. Abnormal metabolism of SGs may contribute to the pathogenesis of (neuro)degenerative diseases such as amyotrophic lateral sclerosis (ALS). Many SG proteins are affected by mutations causative of these conditions, including fused in sarcoma (FUS). Mutant FUS variants have high affinity to SGs and also spontaneously form de novo cytoplasmic RNA granules. Mutant FUS-containing assemblies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…Identifying the components of UV SGs is a key step to understanding these unusual SGs. Biochemical purification strategies and proximity labeling studies have enabled us to understand the proteomic and transcriptomic landscapes of canonical SGs (Jain et al, 2016; Khong et al, 2017; Markmiller et al, 2018; Namkoong et al, 2018; Padrón et al, 2019; Youn et al, 2019; Marmor-Kollet et al, 2020; Matheny et al, 2021; Vu et al, 2021; An et al, 2022). However, parallel studies on UV SGs, or any non-canonical subtype, remain to be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying the components of UV SGs is a key step to understanding these unusual SGs. Biochemical purification strategies and proximity labeling studies have enabled us to understand the proteomic and transcriptomic landscapes of canonical SGs (Jain et al, 2016; Khong et al, 2017; Markmiller et al, 2018; Namkoong et al, 2018; Padrón et al, 2019; Youn et al, 2019; Marmor-Kollet et al, 2020; Matheny et al, 2021; Vu et al, 2021; An et al, 2022). However, parallel studies on UV SGs, or any non-canonical subtype, remain to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological SGs (pSGs) are chronic SGs that form in diseased cells and are hypothesized to seed the accumulation of irreversible and toxic disease aggregates. pSGs have been most closely associated to date with ALS and Alzheimer’s Disease (Vanderweyde et al, 2012, 2016; Ash et al, 2014; Aulas and vande Velde, 2015; Apicco et al, 2018; Zhang et al, 2019; Marmor-Kollet et al, 2020; An et al, 2022). Several excellent reviews have been written on the subject (Wolozin, 2014; Aulas and vande Velde, 2015; Wolozin and Ivanov, 2019), including one within this Research Topic (Rhine et al, 2022).…”
Section: Understanding Sg Subtypesmentioning
confidence: 99%
“…In a recent report, An et al 111 demonstrated that aberrant, persistent pathological stress granules formed by an ALS-associated FUS mutant exhibit different proteomics compared with normal stress granules. These stress granules are characterized by enriched physical interactions between components, consistent with earlier observations that pathological stress granules are less dynamic.…”
Section: Overview Of Condensate Biologymentioning
confidence: 99%
“…A growing number of studies have demonstrated that IFN signaling proteins often re-localize to SG upon viral infection [89,90]. Furthermore, several anti-viral proteins, some of which also ISG, are known constituents of RNP granules including FUS, MOV10, and more recently TDRD3 [90,91]. These observations all raise critical questions regarding SHFL: Does SHFL restrict the expression of select mRNA by re-localizing them to P-bodies as a part of the IFN response?…”
Section: Shiftless and Rna Granules During Dna Virus Infectionmentioning
confidence: 99%